2021
DOI: 10.1016/j.dcn.2021.101009
|View full text |Cite
|
Sign up to set email alerts
|

Predicting multiscan MRI outcomes in children with neurodevelopmental conditions following MRI simulator training

Abstract: Pediatric brain imaging holds significant promise for understanding neurodevelopment. However, the requirement to remain still inside a noisy, enclosed scanner remains a challenge. Verbal or visual descriptions of the process, and/or practice in MRI simulators are the norm in preparing children. Yet, the factors predictive of successfully obtaining neuroimaging data remain unclear. We examined data from 250 children (6–12 years, 197 males) with autism and/or attention-deficit/hyperactivity disorder. Children c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 75 publications
(115 reference statements)
0
12
0
Order By: Relevance
“…Across diagnosis groups, children with more severe social deficits, more inattentive symptoms, more hyperactive/impulsive symptoms, or poorer motor control were more likely to have unusable rs-fMRI data and be excluded, while older children or children with higher intellectual ability were less likely to be excluded for both levels of motion QC. Similarly, Simhal et al (2021) found that children with ASD and children with ADHD who failed a mock MRI training protocol were younger, had lower verbal and non-verbal intelligence scores, and more severe ADOS scores than children with ASD and children with ADHD who passed the training protocol. These findings suggest that the mechanisms driving missingess in rs-fMRI studies may be related to scientifically relevant participant characteristics.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Across diagnosis groups, children with more severe social deficits, more inattentive symptoms, more hyperactive/impulsive symptoms, or poorer motor control were more likely to have unusable rs-fMRI data and be excluded, while older children or children with higher intellectual ability were less likely to be excluded for both levels of motion QC. Similarly, Simhal et al (2021) found that children with ASD and children with ADHD who failed a mock MRI training protocol were younger, had lower verbal and non-verbal intelligence scores, and more severe ADOS scores than children with ASD and children with ADHD who passed the training protocol. These findings suggest that the mechanisms driving missingess in rs-fMRI studies may be related to scientifically relevant participant characteristics.…”
Section: Discussionmentioning
confidence: 86%
“…Scanning these underrepresented populations requires thoughtful experimental accommodations. Some approaches for improving the likelihood of collecting usable data from pediatric participants focus on scan preparation: having a caregiver model scan procedures, practicing in an MRI simulator ( Horien et al, 2020 ; Nordahl et al, 2016 ; Simhal et al, 2021 ), or playing a virtual reality-based MRI game ( Pua et al, 2020 ; Stunden et al, 2021 ). Others focus on modifications during the scan: passive movie-viewing to reduce boredom ( Vanderwal et al, 2019 ), providing real-time feedback to participants using framewise integrated real-time MRI monitoring (FIRMM) software ( Dosenbach et al, 2017 ; Greene et al, 2018 ), or using personalized incentive systems to reward compliance with MRI instructions ( Pua et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Scanning these underrepresented populations requires thoughtful experimental accommodations. Some approaches for improving the likelihood of collecting usable data from pediatric participants focus on scan preparation: having a caregiver model scan procedures, practicing in an MRI simulator (Nordahl et al, 2016; Horien et al, 2020; Simhal et al, 2021), or playing a virtual reality-based MRI game (Stunden et al, 2021; Pua et al, 2020). Others focus on modifications during the scan: passive movie-viewing to reduce boredom (Vanderwal et al, 2019), providing real-time feedback to participants using framewise integrated real-time MRI monitoring (FIRMM) software (Dosenbach et al, 2017; Greene et al, 2018), or using personalized incentive systems to reward compliance with MRI instructions (Pua et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, extensive MRI simulator practice has been used to scan small samples of autistic children with intellectual disabilities (Nordahl et al, 2016), but this places additional burdens on families by requiring multiple visits. In addition, some studies with autistic children have observed that head motion, while reduced after extensive training, is still associated with symptom severity (Simhal et al, 2021; Gabrielsen et al, 2018). Virtual reality-based games played at home may be as effective as MRI simulator training for typically developing children, (Stunden et al, 2021); however, it remains unclear if children with neurodevelopmental disorders would respond similarly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation